An innovative MOOC platform: the implications of self-directed learning abilities to improve motivation in learning and to support self-regulation. Issue 3 (30th April 2021) - Onah, Daniel F.O.; Pang, Elaine L.L.; Sinclair, Jane E.; Uhomoibhi, James
Abstract : Purpose: Massive open online courses (MOOCs) have received wide publicity and many institutions have invested considerable effort in developing, promoting and delivering such courses. However, there are still many unresolved questions relating to MOOCs and their effectiveness in a blended-learning context. One of the major recurring issues raised in both academic literature and in the press about MOOCs is the consistently high dropout rate of MOOC learners. Design/methodology/approach: In this study, we applied mixed methods as an exploratory case study, which prioritised the quantitative and qualitative approaches for the data collection processes. The data were collected using a MOOC Online Self-regulated Learning Questionnaire (MOSLQ) adapted and created from an existing measuring instrument. The quantitative data was analysed using Statistical Package for the Social Sciences (SPSS Version 22) tool to conduct descriptive analysis. The qualitative results obtained from the transcribed focus group interviews in this study revealed the various behavioural patterns of how undergraduate students self-directed their learning. This focus group interview was conducted to reveal the various ways students organised and strategised their learning patterns in order to derive satisfaction in their distinctive learning behaviours and encourage motivation within their study approaches. Quantitative data collected online included a 30 items survey of which 17 respondents completed the survey items in the blended-learning study. The online course survey included 19 items of which data were gathered from 11 respondents. Findings: Across the data, it is noticeable and clear that time management and goal setting were among the dimensions that are highly rated close to high level among SRL skills investigated in this study. We found that goal setting and task strategies predicted much better attainment of individuals controlling personal course goals, while help seeking was associated with lower goal attainment among majority of the participants. Research limitations/implications: The study also identified several challenges. For example, there were some challenges in learners completing the survey questions even when several reminders were sent out forth nightly. At this preliminary stage, learners participated as lurkers without engaging fully with other non-academic and academic interactive activities such as surveys, in course quizzes and forums. Most of the participants in this course said they enrolled to know more about the new trend MOOC, to make friends, to have fun and so on. Although, these are some of their intentions for participating, some of the participants at some points contributed to discussion forums. Practical implications: Our platform currently allows learners to direct their learning within the course and also allow the choice of content prerequisite in order to recommend resources necessary for their learning. This study indicates the necessity to support SRL skills and directing development of self-determination skills among the participants. This study when applied to a larger sample will demonstrate effective measurement on areas of reliability and validity as results from this small sample has indicated some high SRL skill levels for individual learners within the research. Social implications: However, the success of any e-learning or MOOC platform should consider the following best practices and objectives: the learners' entire learning experience, the strategies used in developing the course content, the planning of the course delivery and the methods of delivery. Therefore, all e-learning platforms should be designed with a primary focus on the way students learn to improve their own learning skills and help them regulate their own independent learning habits. In another related study, the success of any e-learning course implementation should be carefully considered with regards to the course's underlying pedagogy and how learners engage with the content. Originality/value: There are many e-learning platforms in existence globally, but little has been mentioned about the development of a MOOC platform in general that could allow independent learning and also adequately demonstrating the components and features used in these MOOC designs. This research's implication is to aid instructional designers to apply best practices in the development of an online course. The best approach in designing a good course is to consider the learners and how they could engage with the course resources independently and develop the ability to self-direct their learning. One of the main goals of e-learning platforms is primarily based on developing learning resources that would be suitable for linear course structure as directed by the course developer or instructor.